International Cooperation as a Prerequisite for Improvement of Access to Orphan Biologic Medicines - Więckowski, Zbigniew (Medicine, Law & Society, 2021)
Rare diseases constitute a global problem. Worldwide, 350 million people suffer from such diseases. The number of diagnosed cases are on the rise. Only a small percentage of those suffering have the opportunity to be treated with modern therapies. Medicines used to treat rare diseases are called orphan drugs. Biologic medicines developed for orphan drug indications, besides patent protection, have a period of regulatory and market exclusivity. After this period of time has elapsed, access to orphan drugs could be improved by the introduction of biosimilar medicines. The biggest challenge is to develop effective legal, tax and economic incentives to stimulate the development of biosimilar medicines for orphan indications. The regulatory agencies - EMA in the EU and the FDA in the USA - play a key role in increasing access to orphan biologics. Undoubtedly, the international cooperation, especially the mutual recognition of registration procedures between countries, and the creation of a common vocabulary and the unification of incentives for the pharmaceutical industry would have the positive impact on access to modern therapies.